The fairy bible : the definitive guide to the world of fairies - Moorey, Teresa (New York : Sterling, 2008)
Fairies of the water, air, and earth, the trees and flowers, the house and hearth: all these mysterious, elusive creatures materialize on the pages of this distinctively beautiful guide to fairyland. --publisher.
The realm of fairies --Water fairies --Air fairies --Fire fairies --Earth fairies --House and hearth fairies --Flower fairies --Tree fairies --Weather fairies --A dictionary of fairies.
Includes index.
Includes bibliographical references (pages 393) and index.
Keywords: Fairies -- Encyclopedias